The relation of saturated fatty acids with low-grade inflammation and cardiovascular disease - Ruiz-Núñez, Begoña; Dijck-Brouwer, D.A. Janneke; Muskiet, Frits A.J. (The Journal of nutritional biochemistry, 2016)
The mantra that dietary (saturated) fat must be minimized to reduce cardiovascular disease (CVD) risk has dominated nutritional guidelines for decades. Parallel to decreasing intakes of fat and saturated fatty acids (SFA), there have been increases in carbohydrate and sugar intakes, overweight, obesity and type 2 diabetes mellitus. The “lipid hypothesis” coined the concept that fat, especially SFA, raises blood low-density lipoprotein-cholesterol and thereby CVD risk. In view of current controversies regarding their adequate intakes and effects, this review aims to summarize research regarding this heterogenic group of fatty acids and the mechanisms relating them to (chronic) systemic low-grade inflammation, insulin resistance, metabolic syndrome and notably CVD. The intimate relationship between inflammation and metabolism, including glucose, fat and cholesterol metabolism, revealed that the dyslipidemia in Western societies, notably increased triglycerides, “small dense” low-density lipoprotein and “dysfunctional” high-density lipoprotein, is influenced by many unfavorable lifestyle factors. Dietary SFA is only one of these, not necessarily the most important, in healthy, insulin-sensitive people. The environment provides us not only with many other proinflammatory stimuli than SFA but also with many antiinflammatory counterparts. Resolution of the conflict between our self-designed environment and ancient genome may rather rely on returning to the proinflammatory/antiinflammatory balance of the Paleolithic era in consonance with the 21st century culture. Accordingly, dietary guidelines might reconsider recommendations for SFA replacement and investigate diet in a broader context, together with nondietary lifestyle factors. This should be a clear priority, opposed to the reductionist approach of studying the effects of single nutrients, such as SFA.